Mobility and gender in vulnerable contexts: The case of the Metropolitan System of Tucumán - Inés González-Alvo; Natalia Czytajlo (Íconos)
This article addresses the concept of urban mobility and the socio-territorial inequalities associated with it. Based on a case study of the Metropolitan System of Tucumán, daily mobility in contexts of vulnerability is analyzed from a theoretical-methodological approach, using quantitative-qualitative techniques and instruments. Opportunity structures (public transportation and care infrastructure); household assets (social plans, vehicles, and driver’s licenses); and mobility practices (trip generation rate and travel modes) are characterized. The data from the Origin and Destination Survey for Tucumán (2012) are used as quantitative inputs and interviews are conducted in a neighborhood representative of high vulnerability in the city, as a source for qualitative analysis. This approach enables an intersectional analysis, insofar as it facilitates an analysis disaggregated by socioeconomic levels and gender. From the analysis of mobility in relation to productive and reproductive spheres, reflections emerge regarding the concept “care mobility”. Finally, after applying an intersectional perspective, the results show differential patterns according to gender and a high vulnerability in women’s mobility. This text is a contribution to the inclusion of a gender perspective in the public policy agenda related to mobility.